ABOUT THE PLAIN ENGLISH MOVEMENT - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Creating law is a complex process. It stems from the constant learning and refinement of knowledge of law - both theory and practice; from recognizing social reality and attitudes and intentions of members of society, but also knowing the state itself inside. The ultimate outcomes of the process of creation of law are “sent” to ordinary citizens, in order to understand them and act according to their content. If we translate the result of this process of law- making into clear, precise and common language written rules of conduct that the average citizen can quickly understand, both the law-making process and its results will be more acceptable to end-users.            The use of specific legal terminology or other professional terminology in the legal acts and rules governing the relations between the addressees need not necessarily be the sole and exclusive channel of communication between the law makers and the addressee. Domestic best-known law theorists constantly emphasize the need to use every day, lively, folk language, with properly “dosed" use of professional terminology, and with appropriate" translation "of the same terminology in every act into the everyday language of the average person. Only in this way, law will  become more understandable, more accepted by the addressee and more respected in the society.            In this paper, we introduce the Plain English movement, inspired by use of the simplest vocabulary when writing legal acts (only in English-speaking countries). The recommendations and guidelines that promminent representatives of this movement make to their lawyers can be applied to a great extent in our, domestic law and in the process of creating our law.
Keywords: Plain English, law making, simplicity, precision, intelligibility